Syarif Hidayatullah's Da'wah and Political Thought: a Religious Moderation Perspective - Juma' (Nur Science Institute, 2025)
This research analyzes Syarif Hidayatullah's da'wah (preaching) and politics using the concept of religious moderation. This research is a library research with main sources, archives, documents, books, journals, and other related works. The sources are obtained from searches on authoritative websites, such as Delpher, British Library, KITLV, and so on. By applying historical analysis, in the form of source criticism, interpretation and historiography, this research uses a biographical approach and leadership theory. This research shows that Syarif Hidayatullah as a scholar and umara has applied the principle of religious moderation in Cirebon Palace. The religious moderation applied by Syarif Hidayatullah is based on religion-based politics. Where, his political policy succeeded in controlling ritual issues, religious ceremonies, da’wah, and socio-politics. Thus, Syarif Hidayatullah not only succeeded as a politician who expanded the territory, but also succeeded in becoming a role model of religious leaders who prioritize the principle of wasathiyah (moderate). Keywords: syarif hidayatullah, political da'wah, moderation REFERENCES Graff and Th. Pigeaud. Islamic Kingdoms in Java, the Transition from Majapahit to Mataram. Translation of Grafitipers and KITLV, First Cet. Jakarta: Temprint, 1985. Suprapto, H. M. Bibit. Encyclopedia of Nusantara Ulama: Life History, Works, and History of Struggle of 157 Nusantara Ulama. Jakarta; Gelegar Media Indonesia, 2009 Ibrahim, Tatang. History of Islamic Culture, Madrasah Tsanawiyah for Class IX Semester 1 and 2. Bandung: CV ARMICO, 2009 Azra, Azyumardi. Network of Middle Eastern and Archipelago Scholars in the XVII and XVIII Centuries; Roots of Indonesian Islamic Reform. Bandung: Mizan, 1994 Bekhofer. Jr, Robert F. A Behavioral Approach to Historical Analysis. New York: Free Press, 1971 Tamburakka, Rustam E. Introduction to Historical Science, Philosophical Theory of History, History of Philosophy and Science and Technology Jakarta: PT Rineka Cipta, 1999 Gottschalk, Louis. Understanding History, ed. Nugroho Notosusanto. Yogyakarta: UI Press Publishing Foundation, 1971 Abdurrahman, Dudung. Historical Research Methods. Jakarta: Logos, 1999 Zuhri, Saifuddin. History of Islamic Revival and Its Development in Indonesia. Bandung: P.T. AL-Maarif, second cet. 1980 Sutrisno, Budiono Hadi. History of the Walisongo Mission of Islamization in Java. Yogyakarta: Graha Pustaka, 2009 Kartodirdjo, Sartono. Introduction to New Indonesian History: From Emporium to Empire Volume I. Jakarta: Gramedia, 1987 Ekajati, Edi S. Local History of West Java. Jakarta: Interumas Sejahtera, 1992 Al Qurtuby, Sumanto. Chinese-Islamic-Javanese Currents. Yogyakarta: Inspeal Ahimsakarya Press, 2003 Sunyoto, Agus. Wali Songo: Reconstructing a Dismissed History. Jakarta: Transpustaka, 2011 Tjandrasasmita, Uka. Archaeology of Islam Nusantara. Jakarta: Gramedia Pustaka Utama, 2009 Sunardjo, RH. Unang. A Glimpse into the History of the Kingdom of Cerbon 1479-1809. Bandung: Tarsito, 1983 Bochari, M. Sanggupri and Wiwi Kuswiah. History of the Traditional Kingdom of Cirebon. Jakarta: CV. Suko Rejo Bersinar, 2001 Wildan, Dadan. Syarif Hidayatullah. Ciputat: Salima, 2012 Siti Fauziyah,